Analysis of Dynamic Response of Composite Reinforcement Concrete Square Piles Under Multi-Directional Seismic Excitation - Chenxi Fu; Gang Gan; Kepeng Chen; Kai Fan (Buildings)
Composite reinforcement concrete square piles exhibit excellent bending resistance and deformation capacity, along with construction advantages such as ease of transportation. In recent years, they have been widely adopted in building pile foundation applications. However, their seismic behavior, particularly under multi-directional excitation, remains inadequately explored. This study employs large-scale shaking table tests to evaluate the seismic response of a single composite reinforcement square pile embedded in a soft clay foundation under different horizontal excitations (0° and 45°) and two distinct ground motions (Wenchuan Songpan and Chi-Chi) to assess directional anisotropy and resonance effects, with explicit consideration of soil–structure interaction (SSI). The key findings include the following: the dynamic earth pressure along the pile exhibits a distribution pattern of “large at the top, small at the middle and bottom”. And SSI reduced pile–soil compression by 20–30% under 45° excitation compared to 0°. The dynamic strain in outer longitudinal reinforcement in pile corners increased by 30–60% under 45° excitation compared to 0°. Under seismic excitation considering SSI, the bending moment along the pile exhibited an “upper-middle maximum” pattern, peaking at depths of 3–5 times the pile diameter. Axial forces peaked at the pile head and decreased with depth. While bending moment responses were consistent between 0° and 45° excitations, axial forces under 45° loading were marginally greater than those under 0°. The Chi-Chi motion induced a bending moment about four times greater than the Songpan motion, highlighting the resonance risks when the ground motion frequencies align with the pile–soil system’s fundamental frequency.